(untitled) (Al-Academy, 2018)
The musical templates are the fundamental reason for admiration and interest among a lot of cultural and societal medias because of the beauty of it’s melodic value, where a lot of Iraqi singing and music specialists and composers try to consolidate daily life idea and translate it into music in a manner that preserve the template and rhythm horizontally and vertically, through the involvement of the scientific and philosophical concepts and theories of modern thought to reach the recipient, as is the theory of form (Gestalt), one of the most important theories that stretched to their interpretations to the field in general art and in music science, especially, as an area that can be manifested as partial components template music, connecting and grasp form and its relationship to portions, where this theory has become a creative process to be able to actually understand the aesthetic process in the Iraqi singing templates secrets, specifically the Iraqi Maqam template, it has dealt with this research a range of related subjects in shape theory (Gestalt), the first chapter included methodological framework for research, represented by the problem and the importance of the research the aim of the research, to identify the shape theory and its applications in the Iraqi Maqam template, and the study of their role in the musical culture in Iraq. The second chapter is the theoretical framework, exemplified by the following axes: (theory of form-Gestalt), and (Iraqi musical templates). While the third chapter included the research methodology, society, and the research samples, and the application of this theory to the Iraqi maqam template, in the fourth chapter the researcher suggested a number of findings and conclusions, and a number of recommendations and suggestions, and finally a list of references